THE ASSOCIATION OF CALCIUM INTAKES AND PREMENSTRUATION SYNDROME AMONG TEENAGE GIRLS IN JAKARTA - A. Harahap, Sarah Reza; Soekatri, Moesijanti (GIZI INDONESIA, 2008)
A recent study (Fikawati, 2005) shows that the intake of calcium among teenages in Bandung was55.8% compared to Indonesian RDA aged 13-19 years (2004), in which for girl only accomplished52.5% from Indonesian RDA. This indicates that teenage girls are vulnerable to the defiicency ofcalcium. Calcium plays an important role to form teeth and bone. Furthermore, calcium is alsoinvolving in cell function regulation as a neurotransmitter, muscle contraction and bloodcoagulation, maintaining the cell membrane permeability and activator for enzyme reactions andhormone secretion. Calcium may also reduce the syndrome that commonly occurs beforemenstruation, usually called pre-menstruation syndrome (PMS). The cross sectional study wasconducted in July 2008 at State Yunior High School 232 Pisangan Timur, Eastern Jakarta. Theaim of the study is to analyze the relationship between calcium intake and PMS among yunior highschool girls students. The subjects were selected purposively and 95 subjects were chosen for thestudy. The results showed that 90,5% of the subjects had calcium intake below the IndonesianRecommended Dietary Allowance (IRDA) and most of them (88.4%) frequently experianced onPMS. The analysis indicated that those who had experienced in PMS was those who had calciumintake lower than 80% from IRDA. The analysis on the food source of calsium using Chi squaretest shows that there is a significant relationship between consumption of tempeh and PMS.Keywords: calcium intake, food pattern, PMS